The potential impacts of anthropogenic and climate changes factors on surface water ecosystem deterioration at Kenyir Lake, Malaysia - Islam, Mir Sujaul; Mohd Khairul Amri, Kamarudin; Noorjima, Abd Wahab; Hafizan, Juahir; Nik Mohd Firdaus, Nik Wan; Muhammad Barzani, Gasim; Mohd Ekhwan, Toriman; Ata, Frankie Marcus; Adiana, Ghazali; Atikah, Anuar; Hanif, Abdullah; Nur Izzati, Hussain; et al. (Science Publishing Corporation, 2018)
Water ecosystem deterioration can be affected by various factors of either natural environment or physical changes in the river basin. Data observation were made during dry season (April 2017) and wet season (December 2017). 21 sampling stations were selected along Kenyir Lake Basin. Overall, the water quality status as stated in NWQS is categorized as Class I on dry season and Class II on wet sea-son. The major pollutants in Kenyir Lake are Total Suspended Solids (TSS), Chemical Oxygen Demand (COD), Dissolve Oxygen and pH which are contributed largely by untreated or partially treated sewage from tourism development and construction activities around the basin. The sedimentation problem level in the Kenyir Lake Basin is not in critically stage but the flow rate of water and land use ac-tivities (development around basin) will be contributed to the increasing levels of sedimentation. The good site management such as the implementation of proper site practice measures to control and treat run-off prior to discharge will ensure that the construction works will not affect the quality and quantity of the receiving waters or have significant impact upon the receiving waters.